Composition and thermoplastic molding compound for producing high gloss moldings
A tailored composition of aromatic polycarbonate and rubber-modified vinyl copolymers with specific ratios and additives addresses the issues of surface gloss and toughness in PC+ABS compounds, providing improved mechanical properties and chemical resistance.
Patent Information
- Application Number
- JP2020551985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-03-28
- Filing Date
- 2019-03-26
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2039-03-26
AI Technical Summary
Existing thermoplastic PC+ABS molding compounds lack sufficient surface gloss, processing stability, and stress cracking resistance, especially under moist and warm conditions, while maintaining good toughness and melt flow properties.
A composition comprising specific ratios of aromatic polycarbonate, rubber-modified vinyl copolymers with controlled particle sizes and glass transition temperatures, along with optional polymeric additives, is used to enhance the properties of thermoplastic molding compounds, including high gloss and improved toughness.
The composition achieves high surface gloss, good toughness, especially at low temperatures, and enhanced stress cracking resistance under chemical exposure, while maintaining processing stability and aging resistance.
Smart Images

Figure 0007599948000001 
Figure 0007599948000002 
Figure 0007599948000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for producing a thermoplastic moulding compound, preferably a polycarbonate composition, to said moulding compound, to the use of said composition or said moulding compound for producing moulded articles, and to the moulded articles themselves. [Background technology]
[0002] Compositions for producing thermoplastic molding compounds, especially polycarbonate compositions, have been known for some time. The compositions and the molding compounds produced therefrom are used for producing moldings for many applications, for example for the automotive, construction and electronics sectors.
[0003] The properties of the molded articles produced from such thermoplastic molding compounds can be tailored to the requirements of each application through the selection of the components of the composition and the range of amounts in which these components are used in the composition.
[0004] Blend partners with elastomeric properties are added to polycarbonates as impact modifiers to increase toughness, especially at low temperatures. Impact modifiers, on the other hand, may differ in the chemical composition of the elastic component, or else in its morphology. In addition, impurities introduced during the production of impact modifiers may affect the properties of the polycarbonate, and thus the polycarbonate composition, as well as the molding compounds and molded articles produced from the polycarbonate.
[0005] Acrylonitrile-butadiene-styrene (ABS) copolymers are widely used as blend partners with elastomeric properties for polycarbonate compositions. In addition to improving further mechanical properties such as toughness at low temperatures and elongation at break in tensile tests, ABS in most cases also promotes the melt flowability of thermoplastic molding compounds made from the polycarbonate compositions, thus facilitating their processing to obtain molded articles.
[0006] In many applications, the molded parts produced are subjected to tension and are simultaneously in contact with chemicals. Under such conditions, failure of the molded parts due to stress cracking can occur. Therefore, stress crack resistance is an additional property to be improved through the use of elastomeric components.
[0007] Acrylonitrile-butadiene-styrene (ABS) copolymers can be produced by free radical polymerization. The commonly used method is bulk polymerization, which results in products of high purity and favorable rheological properties. The high purity of such ABS polymers produced by bulk polymerization allows compositions comprising polycarbonates suitable for producing PC+ABS molding compounds with good stability against certain aging effects, especially improved stability under warm and humid conditions to which molded articles produced from the molding compounds may be exposed during use.
[0008] For example, WO 2007 / 009622 A1 discloses polycarbonate bulk ABS compositions with low lithium content that are notable for improved hydrolytic stability.
[0009] It is also known that modification of the ABS component can further improve the mechanical and rheological properties of polycarbonate ABS molding compounds and thus adapt them to specific requirements.
[0010] WO 01 / 62851 A1 discloses a PC+bulk ABS composition that provides improved processability and improved impact resistance in injection molded parts comprising bulk ABS that comprises star-branched rubber having three or more arms.
[0011] WO 01 / 70884 A1 discloses a PC+bulk ABS composition characterized by reduced anisotropic toughness, comprising bulk ABS having a matrix phase comprising a copolymer of an aromatic monovinylidene monomer, an ethylenically unsaturated nitrile monomer and an ester of acrylic acid, the content of the ester of acrylic acid being in the range of 0.1% to 15% by weight of the copolymer.
[0012] Further optimization can be achieved in polymer blend systems with respect to specific property profiles not only by varying one ABS component used, but also through the mixing of two or more such blend partners.
[0013] WO 2007 / 065577 A1 discloses PC+ABS molding compounds based on a mixture of two different bulk ABS polymers containing free (co)polymers of different molecular weights, which have an improved balance of toughness and melt flowability even at low temperatures, as well as good aging resistance under the influence of moist and warm conditions, good processing stability and good chemical stability.
[0014] The use of ABS produced by bulk polymerization (bulk ABS) makes it possible to obtain PC+ABS compositions with a well-balanced property profile having the above-mentioned advantages. However, this method generally produces ABS polymers that contain relatively coarse rubber-containing graft particles that can adversely affect the surface impression of molded articles produced from such PC+bulk ABS molding compounds. More specifically, the gloss of such PC+bulk ABS compositions or molded articles produced from PC+bulk ABS molding compounds is insufficient for many applications.
[0015] It is therefore desirable to provide a composition for producing thermoplastic PC+bulk ABS molding compounds that can be used to produce molded articles with high surface gloss. Preferably, the composition should further be characterized by a good balance between high flowability and processing stability of the molding compounds produced therefrom, good (notched impact) toughness, especially at low temperatures, and stress crack resistance under the influence of chemicals of the moldings produced from the molding compounds produced therefrom. More preferably, the molding compounds produced therefrom and the moldings produced therefrom should have good aging resistance to exposure to moist and warm conditions.
[0016] More preferably, the elongation at break should also be improved. Summary of the Invention
[0017] It has now been surprisingly discovered that the desired properties are: -comprises or consists of the following components: and the weight ratio of components B and C in the composition is in the range of 20:80 to 90:10, preferably in the range of 40:60 to 85:15, more preferably in the range of 60:40 to 80:20 It has been found that a composition for producing a thermoplastic molding compound comprises: A) at least one polymer selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates; B) a rubber-modified vinyl copolymer, B.1) 80% to 95% by weight based on the rubber-modified vinyl copolymer B, B.1.1) 60% to 90% by weight of styrene based on component B.1; B.1.2) 10% to 40% by weight of acrylonitrile based on component B.1 Structural units obtained from B.2) 5% to 20% by weight, based on the rubber-modified vinyl copolymer B, of one or more elastomeric graft bases having a glass transition temperature of <-50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene. is formed from (i) a dispersed phase, (i.1) rubber particles grafted with a vinyl copolymer composed of structural units B.1; and (i.2) a vinyl copolymer also composed of structural units B.1, incorporated into the rubber particles as a separate dispersed phase A phase consisting of And (ii) a rubber-free vinyl copolymer matrix, not bound to rubber particles and not incorporated into these rubber particles, consisting of structural units B.1 A rubber-modified vinyl copolymer B comprising C) a rubber-modified vinyl copolymer, C.1) 80% to 95% by weight based on the rubber-modified vinyl copolymer C, C.1.1) 60% to 85% by weight of styrene based on component C.1; C.1.2) 10% to 35% by weight of acrylonitrile, based on component C.1; C.1.3) 0.5% to 15% by weight, based on component C.1, of at least one alkyl methacrylate Structural units obtained from C.2) 5% to 20% by weight, based on the rubber-modified vinyl copolymer C, of one or more elastomeric graft bases having a glass transition temperature of <-50°C and containing at least 50% by weight, based on C.2, of structural units derived from 1,3-butadiene. is formed from (iii) a dispersed phase, (iii.1) rubber particles grafted with a vinyl copolymer composed of structural units C.1; and (iii.2) a vinyl copolymer, also composed of structural units C.1, incorporated into the rubber particles as a separate dispersed phase A phase consisting of And (iv) A rubber-free vinyl copolymer matrix consisting of structural units C.1 that is not attached to or incorporated into the rubber particles.
[0018] Preferably, the composition contains component A in an amount of 30% to 90% by weight, more preferably 40% to 80% by weight, and even more preferably 55% to 75% by weight.
[0019] Preferably, the composition comprises component B in an amount of 5% to 50% by weight, preferably 10% to 40% by weight, more preferably 15% to 35% by weight.
[0020] Preferably, the composition comprises component C in an amount of 3% to 40% by weight, preferably 5% to 30% by weight, more preferably 6% to 15% by weight.
[0021] Preferably, the composition comprises as further component D from 0% to 20% by weight, preferably from 0.1% to 10% by weight, more preferably from 0.2% to 5% by weight of a polymer additive.
[0022] Preferably, the composition comprises: 30% by weight to 90% by weight, more preferably 40% by weight to 80% by weight, and even more preferably 55% by weight to 75% by weight of component A; 5% to 50% by weight, preferably 10% to 40% by weight, more preferably 15% to 35% by weight of component B; 3% to 40% by weight, preferably 5% to 30% by weight, more preferably 6% to 15% by weight of component C; As further component D, 0% to 20% by weight, preferably 0.1% to 10% by weight, more preferably 0.2% to 5% by weight of a polymer additive comprising or consisting of:
[0023] Preferably, the composition consists to an extent of at least 90% by weight of components A to D. More preferably, the composition consists exclusively of components A to D.
[0024] More preferably, the composition contains 1.5% to 7.5% by weight, preferably 2.0% to 6.0% by weight, more preferably 2.5% to 4.5% by weight of structural units derived from 1,3-butadiene.
[0025] Ingredient A Component A is a thermoplastic resin or a mixture of different thermoplastic resins selected from at least one polymer from the group consisting of polycarbonates and polyester carbonates.
[0026] Preferably, component A is selected from at least one polymer from the group consisting of aromatic polycarbonates and aromatic polyestercarbonates, and in the most preferred embodiment component A) is an aromatic polycarbonate or a mixture of different aromatic polycarbonates.
[0027] "Polycarbonate" is understood in the present invention to mean both homopolycarbonates and copolycarbonates. These polycarbonates may be linear or branched in the well-known manner. Mixtures of polycarbonates may also be used according to the invention.
[0028] A maximum of 80 mol %, preferably 20 mol % to a maximum of 50 mol %, of the carbonate groups in the polycarbonates used according to the invention are preferably substituted with aromatic dicarboxylic acid ester groups. Polycarbonates of this type which incorporate both acid radicals from carbonic acid and preferably from aromatic dicarboxylic acids in the molecular chain are called aromatic polyestercarbonates.
[0029] The carbonate groups are essentially stoichiometrically and quantitatively replaced with aromatic dicarboxylic acid ester groups, and therefore the molar ratios of the co-reactants are also reflected in the finished polyestercarbonate. The aromatic dicarboxylic acid ester groups can be incorporated randomly or in blocks.
[0030] The thermoplastic polycarbonates, including thermoplastic polyester carbonates, have an average molecular weight Mw, determined by GPC (gel permeation chromatography in methylene chloride with polycarbonate standards), of 15 kg / mol to 50 kg / mol, preferably 20 kg / mol to 35 kg / mol, and more preferably 23 kg / mol to 33 kg / mol.
[0031] The preferred aromatic polycarbonates and / or aromatic polycarbonates are prepared in known manner from diphenols, carbonic acid or carbonic acid derivatives, and, in the case of polyestercarbonates, preferably aromatic dicarboxylic acids or dicarboxylic acid derivatives, and optionally chain terminators and branching agents.
[0032] The details of the manufacture of polycarbonates have been described in numerous patent specifications over the past approximately 40 years. For example, see Schnell, "Chemistry and Physics of Polycarbonates", Polymer Reviews, Volume 9, Interscience Publishers, New York, London, Sydney 1964, D. Freitag, U. Grigo, PR Mueller, H. Nouvertne, BAYER AG, "Polycarbonates" in Encyclopedia of Polymer Science and Engineering, Volume 11, Second Edition, 1988, pages 648-718, and finally U. Grigo, K. Kirchner and PR Mueller "Polycarbonate" [Polycarbonates] in Becker / Braun, Kunststoff-Handbuch [Plastics Handbook], volume 3 / 1, Polycarbonate, Polyacetale, Polyester, Celluloseester [Polycarbonates, Polyacetals, Polyesters, Cellulose Esters], Carl Hanser Verlag Munich, Vienna 1992, pages 117-299.
[0033] Aromatic polycarbonates and polyestercarbonates are prepared, for example, by reacting diphenols with carbonyl halides, preferably phosgene and / or aromatic dicarbonyl halides, preferably benzene dicarbonyl halides, in an interfacial process, optionally using chain terminators and optionally using trifunctional or higher branching agents, to prepare polyestercarbonates by substituting a portion of the carbonic acid derivatives with aromatic dicarboxylic acids or derivatives of dicarboxylic acids, and aromatic dicarboxylic ester structural units according to the carbonate structural units substituted in the aromatic polycarbonates. Another possibility is, for example, the preparation by a melt polymerization process via the reaction of diphenols with diphenyl carbonate.
[0034] Dihydroxyaryl compounds suitable for the preparation of polycarbonates are those of formula (1): HO-Z-OH (1) [During the ceremony, Z is an aromatic radical having 6 to 30 carbon atoms, which may contain one or more aromatic rings, which may be substituted, and which may contain an aliphatic or alicyclic radical, or an alkylaryl or heteroatom as a bridging element.
[0035] Preferably, Z in formula (1) is a radical of formula (2): [ka] [During the ceremony, R 6 and R 7 are independently H, C1-C 18 -Alkyl, C1-C 18 -alkoxy, halogen such as Cl or Br, or in each case optionally substituted aryl or aralkyl, preferably H or C-C 12 -alkyl, more preferably H or C1-C8-alkyl, most preferably H or methyl; X is a single bond, -SO2-, -CO-, -O-, -S-, C1-C6-alkylene, C2-C5-alkylidene or C5-C6-cycloalkylidene which may be substituted with C1-C6-alkyl, preferably methyl or ethyl, and optionally fused to an aromatic ring containing further heteroatoms. 12 -arylene.
[0036] Preferably, X is a single bond, C1-C5-alkylene, C2-C5-alkylidene, C5-C6-cycloalkylidene, -O-, -SO-, -CO-, -S-, -SO2-, or equation (2a): [ka] is a radical.
[0037] Examples of diphenols suitable for the preparation of polycarbonates include hydroquinone, resorcinol, dihydroxydiphenyl, bis(hydroxyphenyl)alkanes, bis(hydroxyphenyl)cycloalkanes, bis(hydroxyphenyl)sulfides, bis(hydroxyphenyl)ethers, bis(hydroxyphenyl)ketones, bis(hydroxyphenyl)sulfones, bis(hydroxyphenyl)sulfoxides, α,α'-bis(hydroxyphenyl)diisopropylbenzene, phthalimides derived from derivatives of isatin or phenolphthalein and their ring-alkylated, ring-arylated and ring-halogenated compounds.
[0038] Preferred diphenols are 4,4'-dihydroxydiphenyl, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)-p-diisopropylbenzene, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, dimethylbisphenol A, bis(3,5-dimethyl-4-hydroxyphenyl)methane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(3,5-dimethyl-4-hydroxyphenyl)sulfone, 2,4-bis(3,5-dimethyl-4-hydroxyphenyl)-2-methylbutane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)-p-diisopropylbenzene, and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane.
[0039] Particularly preferred diphenols are 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane and dimethylbisphenol A.
[0040] Most preferred is 2,2-bis(4-hydroxyphenyl)propane (bisphenol A).
[0041] These and further suitable diphenols are described, for example, in U.S. Pat. No. 3 028 635 A, U.S. Pat. No. 2 999 825 A, U.S. Pat. No. 3 148 172 A, U.S. Pat. No. 2 991 273 A, U.S. Pat. No. 3 271 367 A, U.S. Pat. No. 4 982 014 A and U.S. Pat. No. 2 999 846 A, in DE-A-1 570 703 A, DE-A-2 063 050, DE-A-2 036 052 A, DE-A-2 211 956 A and DE-A-3 832 396 A, in FR-A-561 518 A, in the research paper "H. Schnell, Chemistry and Physics of Polycarbonates, Interscience Publishers, New York, 1989, 1992, 1991, 1992, 1993, 1994, 1995, 1996, 2001, 2002, 2003, 2004, 2005, 2006, 2007, 2009, 2010, 2011, 2012, 2013, 2014, 2015, 2016, 2017, 2019, 2020, 2021, 2022, 2023, 2030, 2031, 2040, 2041, 2042, 2043, 2044, 2045, 2046, 2050, 1964", as well as in JP-A 62039 / 1986, JP-A 62040 / 1986 and JP-A 105550 / 1986.
[0042] In the case of homopolycarbonates only one diphenol is used, in the case of copolycarbonates two or more diphenols are used. The diphenols used, like all other chemicals and auxiliaries added to the synthesis, may be contaminated with impurities resulting from their own synthesis, handling and storage. However, it is desirable to use raw materials of the highest possible purity.
[0043] Examples of suitable carbonic acid derivatives include phosgene or diphenyl carbonate.
[0044] Suitable chain terminators that can be used in the preparation of the polycarbonates are monophenols. Examples of suitable monophenols include phenol itself, alkylphenols such as cresol, p-tert-butylphenol, cumylphenol, and mixtures thereof.
[0045] Preferred chain terminators are linear or branched C1-C30 -alkyl groups, preferably unsubstituted or tert-butyl substituted. Particularly preferred chain terminators are phenol, cumylphenol and / or p-tert-butylphenol.
[0046] The amount of the chain terminator used is preferably 0.1 to 5 mol % based on the moles of the diphenol used in any case. The chain terminator can be added before, during or after the reaction with the carbonic acid derivative.
[0047] Suitable branching agents are the trifunctional or higher compounds known in polycarbonate chemistry, especially those having three or more than three phenolic OH groups.
[0048] Examples of suitable branching agents include 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, tri(4-hydroxyphenyl)phenylmethane, 2,4-bis(4-hydroxyphenylisopropyl)phenol, 2,6-bis(2-hydroxy-5'-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-hydroxyphenyl)methane, tetra(4-(4-hydroxyphenylisopropyl)phenoxy)methane, 1,4-bis((4',4"-dihydroxytriphenyl)methyl)benzene, and 3,3-bis(3-methyl-4-hydroxyphenyl)-2-oxo-2,3-dihydroindole.
[0049] The amount of branching agent for optional use is preferably between 0.05 mol % and 2.00 mol %, relative to the moles of diphenols used in each case.
[0050] The branching agent can be added either initially with the diphenol and chain terminator in the aqueous alkaline phase or dissolved in an organic solvent prior to phosgenation. In the case of the transesterification process, the branching agent is used together with the diphenol.
[0051] Particularly preferred polycarbonates are homopolycarbonates based on bisphenol A, homopolycarbonates based on 1,3-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane and copolycarbonates based on the two monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane.
[0052] Preferred modes of preparation of polycarbonates, including polyestercarbonates, for use according to the invention are the known interfacial processes and the known melt transesterification processes (see, for example, WO 2004 / 063249 A1, WO 2001 / 05866 A1, WO 2000 / 105867, U.S. Pat. No. 5,340,905 A, U.S. Pat. No. 5,097,002 A, U.S. Pat. No. 5,717,057 A (US-A 5,717,057 A)).
[0053] Most preferably used as component A are aromatic polycarbonates based on bisphenol A.
[0054] Component B Component B is B.1) 80% by weight to 95% by weight, preferably 85% by weight to 93% by weight, more preferably 88% by weight to 92% by weight, based on the rubber-modified vinyl copolymer B; B.1.1) 60% to 90% by weight, preferably 65% to 85% by weight, more preferably 70% to 80% by weight, of styrene, based on component B.1; B.1.2) 10% to 40% by weight, preferably 15% to 35% by weight, more preferably 20% to 30% by weight, of acrylonitrile, based on component B.1 Structural units obtained from B.2) 5% by weight to 20% by weight, preferably 7% by weight to 15% by weight, more preferably 8% by weight to 12% by weight of a rubber-modified vinyl copolymer B having a glass transition temperature T g and one or more elastomeric graft bases comprising at least 50% by weight, preferably at least 75% by weight, more preferably 100% by weight, of structural units derived from 1,3-butadiene, relative to B.2. A rubber-modified vinyl copolymer formed from Rubber-modified vinyl copolymer B is (i) a dispersed phase, (i.1) rubber particles grafted with a vinyl copolymer composed of structural units B.1; and (i.2) a vinyl copolymer also composed of structural units B.1, incorporated into the rubber particles as a separate dispersed phase A phase consisting of And (ii) a rubber-free vinyl copolymer matrix, consisting of structural units B.1, which is not bound to the rubber particles and is not incorporated into these rubber particles; The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0055] Preferably, the dispersed phase (i) has a median particle diameter D50 measured by ultracentrifugation of 0.3 to 2.0 μm, more preferably 0.5 to 1.5 μm, especially 0.7 to 1.2 μm.
[0056] Unless otherwise specified in the present invention, the glass transition temperature T g is determined for all components by dynamic differential scanning calorimetry (DSC) according to DIN EN 61006 (1994 edition) at a heating rate of 10 K / min, Tg is determined as the midpoint temperature (tangent method).
[0057] The rubber-modified vinyl copolymers of component B preferably have a melt volume flow rate (MFR) of 2 to 20 g / 10 min, more preferably 3 to 15 g / 10 min, especially 4 to 8 g / 10 min, measured according to ISO 1133 (2012 edition) at 220° C. with a ram load of 10 kg. When a mixture of multiple rubber-modified vinyl copolymers is used as component B, the preferred MFR range refers to the average of the MFRs of the individual components in component B, weighted by the proportion by weight of the components in the mixture.
[0058] Such a rubber-modified vinyl copolymer B is prepared by polymerizing B.1 and B.2 in the above weight proportions, preferably by bulk polymerization.
[0059] The bulk polymerization method preferably employed for the preparation of the rubber modified graft copolymer B comprises both the polymerization of vinyl monomer B.1 and the grafting of the vinyl copolymer thus formed onto the elastomeric graft base B.2. In addition, in this reaction regime, self-organization (phase separation) occurs (i.1) rubber particles grafted with a vinyl copolymer composed of structural units B.1; and (i.2) a vinyl copolymer also composed of structural units B.1, incorporated into the rubber particles as a separate dispersed phase forming a dispersed phase (i) consisting of This rubber-containing dispersed phase (i) is dispersed in a rubber-free vinyl copolymer matrix (ii) consisting of structural units B.1, which is not attached to or incorporated into the rubber particles.
[0060] The rubber-free vinyl copolymer (ii), in contrast to the other vinyl copolymer fractions of component B, can be leached with a suitable solvent, for example acetone.
[0061] The size of the dispersed phase (i) of the rubber-modified vinyl copolymer B thus prepared is controlled via the conditions of the reaction regime, such as, for example, the temperature of the polymer, the resulting viscosity, and the shear resulting from stirring.
[0062] The median particle size D50 is the diameter above which 50% by weight of the particles are greater and below which 50% by weight are smaller. Unless otherwise stated in the present invention, the median particle size is determined for all components by ultracentrifugation measurements (W. Scholtan, H. Lange, Kolloid-Z. und Z. Polymere 250 (1972), 782-796).
[0063] Preferred graft bases B.2 are diene rubbers containing butadiene, or mixtures of diene rubbers containing butadiene, or copolymers of diene rubbers containing butadiene, or mixtures thereof with further copolymerizable monomers (for example according to B.1).
[0064] A particularly preferred graft base B.2 is pure polybutadiene rubber. In a further preferred embodiment, B.2 is a styrene-butadiene block copolymer rubber.
[0065] Preferably, component B has a polybutadiene content of 5% to 18% by weight, more preferably 7% to 14% by weight, especially 8% to 12% by weight.
[0066] Particularly preferred rubber-modified vinyl copolymers of component B are the bulk ABS polymers described, for example, in DE-A-2 035 390A (=U.S. Pat. No. 3 644 574A) or DE-A-2 248 242A (=GB-A-1 409 275A), or in Ullmann's, Enzyklopaedie der Technischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry], Vol. 19 (1980), p. 280 ff.
[0067] The vinyl copolymer (ii) that is not chemically bonded to the rubber base B.2 and not incorporated in the rubber particles may result from the preparation of the graft polymer B in the polymerization, as described above. Similarly, a part of this vinyl copolymer (ii) of the rubber-modified vinyl copolymer component B that is not chemically bonded to the rubber base B.2 and not incorporated in the rubber particles may result from its preparation, while another part may be polymerized separately and added to component B as a constituent of component B. The proportion x(ii) of the vinyl (co)polymer (ii), regardless of its origin, measured as the acetone-soluble fraction in component B, is preferably at least 60% by weight, more preferably at least 70% by weight, and even more preferably at least 75% by weight, relative to component B. The proportion x(ii) of the vinyl copolymer (ii), regardless of its origin, measured as the acetone-soluble fraction in component B, is preferably at most 95% by weight, more preferably at most 90% by weight, and even more preferably at most 85% by weight, relative to component B.
[0068] The vinyl copolymer (ii) in the rubber-modified vinyl copolymer of component B has a weight average molecular weight M w (ii) is preferably 140 to 200 kg / mol, more preferably 150 to 180 kg / mol.
[0069] In the context of the present invention, the weight average molecular weight M of the vinyl copolymer in component B w (ii) is determined by gel permeation chromatography (GPC) in tetrahydrofuran against polystyrene as the standard.
[0070] Preferably, component B does not contain alkali metal salts, alkaline earth metal salts, ammonium salts or phosphonium salts of saturated fatty acids having 8 to 22 carbon atoms, resin acids, alkyl and alkylaryl sulfonic acids, and fatty acid alcohol sulfates.
[0071] Component B preferably contains less than 100 ppm, more preferably less than 50 ppm, and most preferably less than 20 ppm of alkali metal and alkaline earth metal ions.
[0072] Component C Component C is C.1) 80% by weight to 95% by weight, preferably 85% by weight to 93% by weight, more preferably 88% by weight to 92% by weight, based on the rubber-modified vinyl copolymer C; C.1.1) 60% to 85% by weight, preferably 65% to 80% by weight, more preferably 67% to 75% by weight of styrene, based on component C.1; C.1.2) 10% to 35% by weight, preferably 15% to 30% by weight, more preferably 20% to 28% by weight, of acrylonitrile, based on component C.1; C.1.3) 0.5% to 15% by weight, preferably 2% to 8% by weight, more preferably 3% to 6% by weight, of at least one alkyl methacrylate, relative to component C.1; Structural units obtained from C.2) 5% by weight to 20% by weight, preferably 7% by weight to 15% by weight, more preferably 8% by weight to 12% by weight of a rubber-modified vinyl copolymer C having a glass transition temperature T g and one or more elastic graft bases comprising at least 50% by weight, preferably at least 75% by weight, more preferably 100% by weight, of structural units derived from 1,3-butadiene, relative to C.2. A rubber-modified vinyl copolymer formed from Rubber-modified vinyl copolymer C is (iii) a dispersed phase, (iii.1) rubber particles grafted with a vinyl copolymer composed of structural units C.1; and (iii.2) a vinyl copolymer, also composed of structural units C.1, incorporated into the rubber particles as a separate dispersed phase A phase consisting of And (iv) a rubber-free vinyl copolymer matrix consisting of structural units C.1, which is not bound to the rubber particles and is not incorporated into these rubber particles; The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0073] The dispersed phase (iii) has a median diameter D50 measured by ultracentrifugation of preferably 0.3 to 2.0 μm, more preferably 0.4 to 1.5 μm, particularly preferably 0.4 to 0.7 μm.
[0074] The rubber-modified vinyl copolymers of component C preferably have a melt volume flow rate (MFR) of 2 to 60 g / 10 min, more preferably 10 to 50 g / 10 min, especially 20 to 40 g / 10 min, measured according to ISO 1133 (2012 edition) at 220° C. with a ram load of 10 kg. When a mixture of multiple rubber-modified vinyl copolymers is used as component C, the preferred MFR range refers to the average of the MFRs of the individual components weighted by their proportion by mass in the mixture.
[0075] Such a rubber-modified vinyl copolymer C is prepared by polymerizing C.1 and C.2 in the above weight proportions, preferably by bulk polymerization.
[0076] The bulk polymerization method preferably employed for the preparation of the rubber-modified graft copolymer C comprises both the polymerization of vinyl monomers C.1 and the grafting of the vinyl copolymer thus formed onto the elastomeric graft base C.2. In addition, in this reaction regime, self-organization (phase separation) occurs (iii.1) rubber particles grafted with a vinyl copolymer composed of structural units C.1; and (iii.2) a vinyl copolymer, also composed of structural units C.1, incorporated into the rubber particles as a separate dispersed phase forming a dispersed phase (iii) consisting of This rubber-containing dispersed phase (iii) is dispersed in a rubber-free vinyl copolymer matrix (iv) consisting of structural units C.1, which is not attached to the rubber particles and is not incorporated into these rubber particles.
[0077] The rubber-free vinyl copolymer (iv), in contrast to the other vinyl copolymer fractions of component C, can be leached with a suitable solvent, for example acetone.
[0078] The size of the dispersed phase (iv) of the rubber-modified vinyl copolymer C thus prepared is controlled via the conditions of the reaction regime, such as, for example, the temperature of the polymer, the resulting viscosity, and the shear resulting from stirring.
[0079] The median particle size D50 is the diameter above which 50% by weight of the particles are greater and below which 50% by weight are smaller. Unless otherwise stated in the present invention, the median particle size is determined for all components by ultracentrifugation measurements (W. Scholtan, H. Lange, Kolloid-Z. und Z. Polymere 250 (1972), 782-796).
[0080] Monomer C.1.3 is an alkyl methacrylate, preferably a (C1-C8)-alkyl methacrylate.
[0081] Further preferred monomers C.1.3 are methyl methacrylate, ethyl methacrylate, n-butyl acrylate and tert-butyl acrylate. Most preferably, C.1.3 is n-butyl acrylate.
[0082] Preferred graft bases C.2 are diene rubbers containing butadiene, or mixtures of diene rubbers containing butadiene, or copolymers of diene rubbers containing butadiene, or mixtures thereof with further copolymerizable monomers (for example according to C.1).
[0083] A particularly preferred graft base C.2 is a pure polybutadiene rubber. In a further preferred embodiment, C.2 is a styrene-butadiene block copolymer rubber.
[0084] Component C has a polybutadiene content of preferably 5% by weight to 18% by weight, more preferably 7% by weight to 14% by weight, and particularly preferably 8% by weight to 12% by weight.
[0085] Particularly preferred rubber-modified vinyl copolymers of component B can be prepared analogously to the disclosures in DE-A-2 035 390A (=U.S. Pat. No. 3 644 574A) or DE-A-2 248 242A (=GB Pat. No. 1 409 275A) or Ullmann's, Enzyklopaedie der Technischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry], Vol. 19 (1980), p. 280 ff.
[0086] The vinyl copolymer (iv) that is not chemically bonded to the rubber base C.2 and not incorporated in the rubber particles may result from the preparation of the graft polymer C in the polymerization, as described above. Similarly, a part of this vinyl copolymer (iv) of the rubber-modified vinyl copolymer component C that is not chemically bonded to the rubber base C.2 and not incorporated in the rubber particles may result from its preparation, while another part may be polymerized separately and added to component C as a constituent of component C. The proportion x(iv) of the vinyl copolymer (iv), regardless of its origin, measured as the acetone-soluble fraction in component C, is preferably at least 60% by weight, more preferably at least 70% by weight, and even more preferably at least 75% by weight, relative to component C. The proportion x(iv) of the vinyl (co)polymer (iv), regardless of its origin, measured as the acetone-soluble fraction in component C, is preferably at most 95% by weight, more preferably at most 90% by weight, and even more preferably at most 85% by weight, relative to component C.
[0087] The vinyl copolymer (iv) in the rubber-modified vinyl copolymer of component C preferably has a weight average molecular weight M w (iv) is 110-130 kg / mol.
[0088] In the context of the present invention, the weight average molecular weight M of the vinyl copolymer in component C w (iv) is determined by gel permeation chromatography (GPC) in tetrahydrofuran against polystyrene as the standard.
[0089] Component C preferably does not contain alkali metal, alkaline earth metal, ammonium or phosphonium salts of saturated fatty acids having 8 to 22 carbon atoms, resin acids, alkyl and alkylaryl sulfonic acids, and fatty acid alcohol sulfates.
[0090] Component C preferably contains less than 100 ppm, more preferably less than 50 ppm, and most preferably less than 20 ppm of alkali metal and alkaline earth metal ions.
[0091] Components B and C each comprise a vinyl polymer matrix having the molecular weights Mw(ii) and Mw(iv) specified above, which results in an average molecular weight gMw calculated by the formula: gMw=[x(ii)·Mw(ii)·x(B)+x(iv)·Mw(iv)·x(C)] / [x(ii)·x(B)+x(iv)·x(C)] Where: Mw(ii) is the average molecular weight Mw of the vinyl copolymer matrix (ii) in component B, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard; x(B) is the proportion of component B in the composition in weight percent; Mw(iv) is the average molecular weight Mw of the vinyl copolymer matrix (iv) in component C, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard; x(C) is the proportion of component C in the composition in weight percent.
[0092] The average molecular weight gMw is preferably in the range of 125 to 160 kg / mol, more preferably in the range of 135 to 155 kg / mol, and even more preferably in the range of 140 to 150 kg / mol.
[0093] Preferably, the dispersed phase (i) in component B and the dispersed phase (iii) in component C have the above-mentioned median particle size D50. More preferably, at least one of the two dispersed phases (i) and (iii) has a median particle size D50 of 0.7 to 1.5 μm, as measured by ultracentrifugation.
[0094] Component D As component D, the composition according to the invention may comprise one or more polymeric additives, preferably selected from the group consisting of flame retardants, anti-drip agents, flame retardant synergists, smoke inhibitors, lubricants and release agents, nucleating agents, antistatic agents, conductive additives, stabilizers (e.g. hydrolysis, heat ageing and UV stabilizers, and transesterification inhibitors), flow promoters, compatibilizers, further impact modifiers other than components B and C (with or without core-shell structure, e.g. methyl methacrylate-butadiene-styrene copolymers with core-shell structure (MBS) prepared by emulsion polymerization), further polymeric building blocks other than components A, B and C (e.g. functional blend partners), fillers and reinforcing agents, and dyes and pigments.
[0095] In a preferred embodiment, the composition does not include any fillers or reinforcing agents.
[0096] In a preferred embodiment, the composition comprises at least one polymer additive selected from the group consisting of lubricants and mold release agents, stabilizers, flow promoters, compatibilizers, additional impact modifiers, additional polymeric components, dyes and pigments.
[0097] In a preferred embodiment, the composition includes pentaerythritol tetrastearate as a mold release agent.
[0098] In a preferred embodiment, the composition comprises as stabilizer at least one representative selected from the group consisting of sterically hindered phenols, organic phosphites and sulfur-based co-stabilizers.
[0099] In a particularly preferred embodiment, the composition comprises as stabilizer at least one representative selected from the group consisting of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl)phosphite.
[0100] In a particularly preferred embodiment, the composition comprises as component D at least one representative selected from the group consisting of lubricants and release agents, stabilizers, flow promoters and dyes and pigments, and does not comprise other polymeric additives of component D.
[0101] In a further preferred embodiment, the composition comprises, as component D, at least one release agent, at least one stabilizer and optionally at least one dye and / or one pigment, without further polymeric additives of component D.
[0102] When the composition contains as component D or as a constituent of component D a graft polymer prepared by emulsion polymerization, it is used in a weight proportion not exceeding preferably 15% of the sum of the weight proportions of components B and C, more preferably 10% of the sum of the weight proportions of components B and C, and even more preferably 7% by weight of the sum of the weight proportions of components B and C.
[0103] More preferably, the composition comprises, as component D, a graft polymer prepared by emulsion polymerization in an amount of 6% by weight or less, preferably 4% by weight or less, more preferably 2% by weight or less. In the most preferred embodiment, the composition does not comprise a graft polymer or another polymer prepared by emulsion polymerization.
[0104] Manufacturing of molding compounds and molded articles The composition according to the invention can be used to produce thermoplastic molding compounds.The thermoplastic molding compounds according to the invention can be produced, for example, by mixing the components of the composition and melt-kneading and melt-extrusion in known manner in conventional equipment such as internal kneaders, extruders and twin-screw systems, preferably at temperatures between 200°C and 320°C, more preferably between 240°C and 310°C, most preferably between 260°C and 300°C.In the context of the present application, this process is generally called compounding.
[0105] The term molding compound is therefore understood to mean the product obtained when the components of the composition are melt-kneaded and melt-extruded.
[0106] The individual components of the composition can be mixed in known manner, either successively or simultaneously, at temperatures of about 20° C. (room temperature) or higher, which means, for example, that some components can be added through the main intake of an extruder, while the remaining components can then be added to the compounding process through an auxiliary extruder.
[0107] The molding compounds according to the invention can be used to produce all kinds of moldings. They can be produced, for example, by injection molding, extrusion and blow molding processes. Another form of processing is the production of moldings by thermoforming from previously produced sheets or films. The molding compounds according to the invention are particularly suitable for processing by extrusion, blow molding and thermoforming processes.
[0108] The composition can also be metered directly into an injection molding machine or extrusion unit and processed into moldings.
[0109] Examples of such moldings which can be produced from the compositions and moulding compounds according to the invention are films, profiles, housing parts of all kinds, for household appliances such as juice presses, coffee machines, mixers, for office equipment such as monitors, flat screens, notebooks, printers, copiers, sheets, pipes, electrical installation ducts, profiles for windows, doors and other construction sectors (internal fitout and external applications), electrical and electronic parts such as switches, plugs, sockets, parts for commercial vehicles, in particular for the automotive sector. The compositions according to the invention are also suitable for the production of the following moldings or mouldings: interior fitting parts for rail vehicles, ships, aircraft, buses and other motor vehicles, bodywork components for motor vehicles, housings for electrical equipment with mini-transformers, housings for equipment for processing and transmitting information, housings and surface finishes for medical equipment, massage machines and housings therefor, children's motor toys, seat-like wall elements, housings for safety devices, thermally insulated transport containers, moulded parts for sanitary and bathroom equipment, protective grilles for ventilation openings and housings for garden tools.
[0110] Further embodiments 1 to 41 of the present invention are described below. 1. A composition for producing a thermoplastic molding compound, comprising the following components: A) at least one polymer selected from the group consisting of polycarbonates and polyestercarbonates; B) a rubber-modified vinyl copolymer, B.1) 80% to 95% by weight based on rubber-modified vinyl copolymer B, B.1.1) 60% to 90% by weight of styrene based on component B.1; B.1.2) 10% to 40% by weight of acrylonitrile based on component B.1 Structural units obtained from B.2) 5% to 20% by weight, based on the rubber-modified vinyl copolymer B, of one or more elastomeric graft bases having a glass transition temperature of <-50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene. is formed from (i) a dispersed phase, (i.1) rubber particles grafted with a vinyl copolymer composed of structural units B.1; and (i.2) a vinyl copolymer also composed of structural units B.1, incorporated into the rubber particles as a separate dispersed phase A phase consisting of And (ii) a rubber-free vinyl copolymer matrix not bound to or incorporated into rubber particles, consisting of structural units B.1; A rubber-modified vinyl copolymer B comprising C) a rubber-modified vinyl copolymer, C.1) 80% to 95% by weight based on the rubber-modified vinyl copolymer C, C.1.1) 60% to 85% by weight of styrene based on component C.1; C.1.2) 10% to 35% by weight of acrylonitrile, based on component C.1; C.1.3) 0.5% to 15% by weight, based on component C.1, of at least one alkyl methacrylate Structural units obtained from C.2) 5% to 20% by weight based on said rubber-modified vinyl copolymer C of one or more elastomeric graft bases having a glass transition temperature of <-50°C and containing at least 50% by weight based on C.2 of structural units derived from 1,3-butadiene is formed from (iii) a dispersed phase, (iii.1) rubber particles grafted with a vinyl copolymer composed of structural units C.1; and (iii.2) a vinyl copolymer, also composed of structural units C.1, incorporated into the rubber particles as a separate dispersed phase A phase consisting of And (iv) a rubber-free vinyl copolymer matrix consisting of structural units C.1, which is not bound to the rubber particles and is not incorporated into these rubber particles; A rubber-modified vinyl copolymer C comprising comprising or consisting of The weight ratio of components B and C is in the range of 20:80 to 90:10. composition.
[0111] 2. The composition of embodiment 1, wherein component A is selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates.
[0112] 3. The composition of embodiment 2, wherein an aromatic polycarbonate based on bisphenol A is used as component A.
[0113] 4. The composition according to any of the previous embodiments, wherein component A has an average molecular weight Mw, measured by gel permeation chromatography in methylene chloride using polycarbonate as standard, of 23 000 g / mol to 33 000 g / mol.
[0114] 5. component B comprises a rubber-free vinyl copolymer matrix (ii) consisting of structural units B.1, which is not bound to the rubber particles and is not incorporated in these rubber particles, in a proportion x(ii) of 60% to 95% by weight, relative to B; Component C comprises a rubber-free vinyl copolymer matrix (iv) consisting of structural units C.1, which is not bound to the particles and is not incorporated into these rubber particles, in a proportion x(iv) of 60% to 95% by weight relative to C. The composition of any of the preceding embodiments.
[0115] 6.Average molecular weight gMw gMw=[x(ii)·Mw(ii)·x(B)+x(iv)·Mw(iv)·x(C)] / [x(ii)·x(B)+x(iv)·x(C)] is in the range of 125-160 kg / mol, Where: Mw(ii) is the average molecular weight Mw of the vinyl copolymer matrix (ii) in component B, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard; x(B) is the proportion of component B in the composition in weight percent; Mw(iv) is the average molecular weight Mw of the vinyl copolymer matrix (iv) in component C, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard; x(C) is the proportion of component C in the composition in weight percent 6. The composition of embodiment 5.
[0116] 7. The composition of embodiment 6, wherein gMw is in the range of 135 to 155 kg / mol.
[0117] 8. The composition of embodiment 6, wherein gMw is in the range of 140 to 150 kg / mol.
[0118] 9. The composition according to any of the previous embodiments, wherein the vinyl copolymer matrix (ii) has an average molecular weight Mw, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard, of 140 to 200 kg / mol.
[0119] 10. The composition according to any of the previous embodiments, wherein the vinyl copolymer matrix (ii) has an average molecular weight Mw, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard, of 150 to 180 kg / mol.
[0120] 11. The composition according to any of the previous embodiments, wherein the vinyl copolymer matrix (iv) has an average molecular weight Mw, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard, of 110 to 130 kg / mol.
[0121] 12. The composition of any of the previous embodiments, wherein component C.1.3 is selected from the group consisting of methyl methacrylate, ethyl methacrylate, n-butyl acrylate, and tert-butyl acrylate.
[0122] 13. The composition of any of the previous embodiments, wherein component C.1.3 is n-butyl acrylate.
[0123] 14.C.1.1) in an amount of 65% to 80% by weight based on component C.1, C.1.2) in an amount of 15% to 30% by weight based on component C.1, C.1.3) in an amount of 2% to 8% by weight based on component C.1 The composition of any of the preceding embodiments.
[0124] 15.C.1.1) in an amount of 67% to 75% by weight based on component C.1; C.1.2) in an amount of 20% to 28% by weight based on component C.1, C.1.3) in an amount of 3% to 6% by weight based on component C.1 The composition of any of the preceding embodiments.
[0125] 16.55 to 75% by weight of component A The composition of any of the preceding embodiments, comprising:
[0126] 17. 15 to 35% by weight of component B The composition of any of the preceding embodiments, comprising:
[0127] 18.6 to 15% by weight of component C The composition of any of the preceding embodiments, comprising:
[0128] 19. 30 to 90% by weight of component A; 5 to 50% by weight of component B; 3 to 40% by weight of component C; 0 to 20% by weight of polymer additives as further component D 16. The composition according to any one of the preceding embodiments 1 to 15, comprising:
[0129] 20. 40 to 80% by weight of component A; 10 to 40% by weight of component B; 5 to 30% by weight of component C; 0.1 to 10% by weight of a polymer additive as further component D 16. The composition according to any one of the preceding embodiments 1 to 15, comprising:
[0130] 21. 0.2 to 5% by weight of component D The composition of any of the preceding embodiments, comprising:
[0131] 22.55 to 75% by weight of component A; 15 to 35% by weight of component B, 6 to 15% by weight of component C; 0.2 to 5% by weight of a polymer additive as further component D The composition of any of the preceding embodiments, comprising:
[0132] 23. The composition of any of the preceding embodiments comprising 1.5% to 7.5% by weight of structural units derived from 1,3-butadiene.
[0133] 24. The composition of any of the previous embodiments comprising 2.0% to 6.0% by weight of structural units derived from 1,3-butadiene.
[0134] 25. The composition of any of the preceding embodiments comprising 2.5% to 4.5% by weight of structural units derived from 1,3-butadiene.
[0135] 26. The composition of any of the preceding embodiments, wherein components B and C are present in a weight ratio of 40:60 to 85:15.
[0136] 27. The composition of any of the preceding embodiments, wherein components B and C are present in a weight ratio of 60:40 to 80:20.
[0137] 28. The composition according to any of the preceding embodiments, wherein the dispersed phase (i) of component B has a median diameter D50, measured by ultracentrifugation, of 0.3 to 2.0 μm, and the dispersed phase (iii) of component C has a median diameter D50, measured by ultracentrifugation, of 0.3 to 2.0 μm.
[0138] 29. The composition according to any of the previous embodiments, wherein at least one of the two dispersed phases (i) and (iii) has a median diameter D50 measured by ultracentrifugation of 0.7 to 1.5 μm.
[0139] 30. The composition of any of the previous embodiments, wherein components B and C do not include alkali metal salts, alkaline earth metal salts, ammonium salts or phosphonium salts of saturated fatty acids having 8 to 22 carbon atoms, resin acids, alkyl and alkylaryl sulfonic acids, and fatty acid alcohol sulfates.
[0140] 31. The composition of any of the previous embodiments, wherein components B and C each contain less than 20 ppm of alkali metal and alkaline earth metal ions.
[0141] 32. The composition of any of the previous embodiments, wherein components B and C are each prepared by bulk polymerization.
[0142] 33. The composition according to any of the previous embodiments, wherein components B.2 and C.2 consist exclusively of structural units derived from 1,3-butadiene.
[0143] 34. The composition according to any of the preceding embodiments, wherein components B and C each have a content of structural units derived from 1,3-butadiene of 8% by weight to 12% by weight.
[0144] 35. The composition according to any of the previous embodiments comprising as component D at least one additive selected from the group consisting of flame retardants, anti-drip agents, flame retardant synergists, smoke suppressants, lubricants and release agents, nucleating agents, antistatic agents, conductive additives, stabilizers, flow promoters, compatibilizers, further impact modifiers other than components B and C, further polymeric constituents other than components A, B and C, fillers and reinforcing agents, and dyes and pigments.
[0145] 36. The composition according to any of the previous embodiments, comprising as component D at least one additive selected from the group consisting of flame retardants, lubricants and release agents, stabilizers, flow promoters, compatibilizers, and dyes and pigments.
[0146] 37. The composition of any of the previous embodiments, which does not include any additional graft polymer prepared by emulsion polymerization.
[0147] 38. The composition according to any of the previous embodiments, consisting of components A-D to the extent of at least 90% by weight.
[0148] 39. A composition according to any of the previous embodiments, consisting of components A-D.
[0149] 40. A molding compound made from the composition of any one of embodiments 1-39.
[0150] 41. A molded article obtained from the composition according to any one of embodiments 1 to 39 or the molding material according to embodiment 40. EXAMPLES
[0151] Ingredient A Based on bisphenol A, the weight average molecular weight M (measured by GPC at room temperature in methylene chloride as solvent against BPA-PC standard) W is a linear polycarbonate with a molecular weight of 30 000 g / mol.
[0152] Ingredient B-1 An acrylonitrile (A)-butadiene (B)-styrene (S) polymer prepared by bulk polymerization and containing a dispersed phase consisting of rubber particles grafted with acrylonitrile copolymers and mainly composed of pure polybutadiene rubber as the graft base, with styrene-acrylonitrile copolymer inclusions and a styrene-acrylonitrile copolymer matrix not bonded to the rubber. Component B-1 has an A:B:S ratio of 23:9:68% by weight and a gel content, calculated as the fraction insoluble in acetone, of 20% by weight. Thus, the tetrahydrofuran-soluble styrene-acrylonitrile copolymer in component B-1 is present in a proportion x(ii) of 80% by weight and has a weight average molecular weight M w (measured by GPC in tetrahydrofuran with polystyrene as standard solvent) is 160 kg / mol. The median particle size value D50 of the dispersed phase is 0.9 μm, measured by ultracentrifugation. The melt flow rate (MFR) of component B-1 is 6.5 g / 10 min, measured at 220 °C with a ram load of 10 kg according to ISO 1133 (2012 edition).
[0153] Ingredient B-2 An acrylonitrile (A)-butadiene (B)-styrene (S) polymer prepared by bulk polymerization, containing a dispersed phase consisting of rubber particles mainly composed of styrene-butadiene block copolymer rubber grafted with styrene-acrylonitrile copolymer and having a butadiene content of 75% by weight, styrene-acrylonitrile copolymer inclusions and a styrene-acrylonitrile copolymer matrix not bonded to the rubber. Component B-2 has an A:B:S ratio of 22:10:68% by weight and a gel content, calculated as the proportion insoluble in acetone, of 19% by weight. Thus, the tetrahydrofuran-soluble styrene-acrylonitrile copolymer in component B-2 is present in a proportion x(ii) of 81% by weight and has a weight average molecular weight M w(measured by GPC in tetrahydrofuran with polystyrene as the standard solvent) is 110 kg / mol. The melt flow rate (MFR) of component B-2 is 30 g / 10 min, measured at 220°C with a ram load of 10 kg according to ISO 1133 (2012 edition).
[0154] Component C-1 An acrylonitrile (A)-butadiene (B)-styrene (S)-n-butyl acrylate (BA) polymer prepared by bulk polymerization and grafted with styrene-acrylonitrile-n-butyl acrylate copolymer, containing a dispersed phase consisting of rubber particles mainly composed of pure polybutadiene rubber as the graft base, with inclusions of styrene-acrylonitrile-n-butyl acrylate copolymer and a styrene-acrylonitrile-n-butyl acrylate copolymer matrix not bonded to the rubber. Component C-1 has an A:B:S:BA ratio of 22.5:10:63:4.5% by weight and a gel content, calculated as the fraction insoluble in acetone, of 19% by weight. Thus, the tetrahydrofuran-soluble styrene-acrylonitrile-n-butyl acrylate copolymer in component C-1 is present in a proportion x(iv) of 81% by weight and has a weight average molecular weight M w The molecular weight (measured by GPC in tetrahydrofuran with polystyrene as standard solvent) is 115 kg / mol. The median particle size value D50 of the dispersed phase is 0.5 μm, measured by ultracentrifugation. The melt flow rate (MFR) of component C-1 is 28 g / 10 min, measured at 220 °C with a ram load of 10 kg according to ISO 1133 (2012 edition).
[0155] Component D-1 Pentaerythritol Tetrastearate
[0156] Component D-2 Irganox™ B900 (BASF, Ludwigshafen, Germany) A mixture of 80% by weight of tris(2,4-di-tert-butylphenyl)phosphite (Irgafos™ 168) and 20% by weight of 2,6-di-tert-butyl-4-(octadecanoxycarbonylethyl)phenol (Irganox™ 1076).
[0157] Preparation and testing of the moulding compounds according to the invention The components were mixed in a Coperion, Werner & Pfleiderer ZSK25 twin-screw extruder (Stuttgart, Germany) at a melt temperature of 260° C. and a vacuum of 10 mbar (absolute). Molded parts were produced in an Arburg 270E injection molding machine at 260° C. or 300° C. and a mold temperature of 80° C.
[0158] The IZOD notched impact strength was measured at -30°C according to ISO 180-1A (1982 edition) on ten test specimens with dimensions of 80 mm x 10 mm x 4 mm each and recorded as the average value of ten individual measurements.
[0159] The elongation at break was measured according to ISO 527 (1996 edition) at room temperature.
[0160] In order to simulate particularly important thermo-mechanical conditions, the measure used for the thermo-mechanical stability was the retention of low-temperature ductility measured on specimens with dimensions 60 mm x 60 mm x 2 mm produced by injection molding at a high melt temperature of 300 °C. For 10 specimens thus produced, the low-temperature ductility was checked in a puncture test at -30 °C, with the specimens lubricated, according to ISO 6603-2 (April 2002 edition). The evaluation criterion used here for low-temperature ductility was the percentage of individual tests resulting in a fracture profile without cracks or with stable cracks, i.e. with an evaluation of the fracture profile "YD" (yield followed by deep drawing, Fig. 1 of ISO 6603-2) or "YS" (yield followed by at least a partial stable crack, Fig. 2 of ISO 6603-2), according to the details in § 3.10 of ISO 6603-2 (April 2002 edition).
[0161] The melt viscosity as a measure of melt fluidity was measured at a temperature of 260°C and a shear rate of 1000 s in accordance with ISO 11443 (2014 edition). -1 was measured.
[0162] The measure used for chemical resistance was the stress crack resistance (ESC) in rapeseed oil. The time to stress crack induced failure at room temperature of specimens with dimensions 80 mm x 40 mm x 4 mm, injection moulded at a melt temperature of 260 °C, was measured by subjecting the specimens to an outer fibre strain of 2.4% using a clamping template and completely immersing them in rapeseed oil. The measurements were carried out according to DIN EN ISO 22088 (2006 edition). After 7 days (168 h), the measurements were stopped if no failure had occurred within that period (in this case the measurements were recorded as >168 h).
[0163] The surface gloss, measured at a viewing angle of 60°, was determined in accordance with DIN 67530 (1982 edition) using a Haze-Gloss device from BYK-Gardner GmbH (Geretsried, Germany) in reflection on test specimens with dimensions 60 mm x 60 mm x 2 mm injection-molded at a melt temperature of 300° C. High-gloss polished injection moldings were used to manufacture these test specimens.
[0164] Tables 1 and 2 summarize the properties of the compositions of the invention and comparative compositions and the moulded articles produced therefrom. Table 1 lists those compositions which, due to a PC:ABS ratio of 70:30 parts by weight, have a Vicat B / 120 heat strain resistance in the region of 129°C + / - 2°C, measured according to ISO 306 (2013 edition) on a test piece with dimensions 80 mm x 10 mm x 4 mm, with a ram load of 50 N and a heating rate of 120°C / h. Table 1 summarizes those compositions which, due to a PC:ABS ratio of 60:40 parts by weight, have a Vicat B / 120 in the region of 120°C + / - 5°C. Due to the different heat strain resistances, the compositions of Tables 1 and 2 are suitable for different applications and therefore cover the various material classes defined in the automotive industry.
[0165] [Table 1]
[0166] [Table 2]
[0167] The data in Tables 1 and 2 show that compositions 2 to 4 according to the invention compared to comparative composition V1, and compositions 6 to 8 according to the invention compared to comparative compositions V5 and V9 to V11, have a surprisingly high gloss and therefore achieve the objectives of the invention.
[0168] Furthermore, the data show that inventive composition 6 has improved elongation at break compared to comparative composition V10, and inventive compositions 6 and 7 have improved flowability compared to comparable comparative compositions V10 and V11. These improvements are not accompanied by a deterioration in processing stability, low temperature ductility and chemical stability, and thus the inventive compositions not only provide improved gloss compared to the comparative compositions, but also provide an improved balance of melt flowability, chemical stability / stress crack resistance low temperature ductility, elongation at break and processing stability.
[0169] It has been found that while compositions 2-4 and 6-8 of the present invention all exhibit improved gloss and thus achieve the primary objective of the present invention, compositions 2 and 3 are preferred over 4, which in turn is preferred over 3, which in turn is preferred over 6 and 7, which in turn is preferred over 8, which in turn is preferred over 7, in terms of the balance between low temperature ductility and chemical stability / stress crack resistance.
Claims
1. A composition for producing a thermoplastic molding compound, comprising the following components: A) at least one polymer selected from the group consisting of polycarbonates and polyestercarbonates; B) a rubber-modified vinyl copolymer, B. 1) 85% to 93% by weight based on the rubber-modified vinyl copolymer B, B.1.1) 65% to 85% by weight of styrene, based on component B.1; B.1.2) 15% to 35% by weight, based on component B.1, of structural units derived from acrylonitrile; B.2) 7% to 15% by weight, based on said rubber-modified vinyl copolymer B, of one or more elastomeric graft bases having a glass transition temperature of <-50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene, formed by a bulk polymerization process; (i) a dispersed phase (i.1) rubber particles grafted with a vinyl copolymer composed of structural units B.1; and (i.2) a vinyl copolymer phase, also composed of structural units B.1, incorporated in the rubber particles as a separate dispersed phase; And (ii) a rubber-modified vinyl copolymer B comprising a rubber-free vinyl copolymer matrix not bound to or incorporated into rubber particles, the rubber-modified vinyl copolymer B being composed of structural units B.1; C) a rubber-modified vinyl copolymer, C. 1) 85% to 93% by weight based on the rubber-modified vinyl copolymer C, C.1.1) 60% to 75% by weight of styrene, based on component C.1; C.1.2) 15% to 30% by weight of acrylonitrile, based on component C.1; C.1.3) 2% to 8% by weight, based on component C.1, of structural units resulting from n-butyl acrylate; C.2) 7% to 15% by weight based on said rubber-modified vinyl copolymer C, one or more elastomeric graft bases having a glass transition temperature of <-50°C and containing at least 50% by weight based on C.2 of structural units derived from 1,3-butadiene, formed by a bulk polymerization process; (iii) a dispersed phase, (iii.1) rubber particles grafted with a vinyl copolymer composed of structural units C.1; and (iii.2) a vinyl copolymer phase, also composed of structural units C.1, incorporated in the rubber particles as a separate dispersed phase; And (iv) A rubber-modified vinyl copolymer C comprising a rubber-free vinyl copolymer matrix that is not bonded to or incorporated into rubber particles and that is composed of structural units C.
1. comprising or consisting of The weight ratio of components B and C is in the range of 20:80 to 90:10; component B comprises a rubber-free vinyl copolymer matrix (ii) consisting of structural units B.1, not bound to the rubber particles and not incorporated in these rubber particles, in a proportion x(ii) of 60% to 95% by weight, relative to B; Component C comprises a rubber-free vinyl copolymer matrix (iv) consisting of structural units C.1, not bound to the rubber particles and not incorporated in these rubber particles, in a proportion x(iv) of 60% to 95% by weight, relative to C; 30 to 90% by weight of component A, 5 to 50% by weight of component B, 3 to 40% by weight of component C, 0 to 20% by weight of polymer additives as further component D and comprising 1.5% by weight to 7.5% by weight of structural units derived from 1,3-butadiene; composition.
2. 2. The composition of claim 1, wherein components B and C are each prepared by bulk polymerization.
3. Average molecular weight gMw gMw=[x(ii) Mw(ii) x(B) + x(iv) Mw(iv) x(C)] / [x(ii) x(B) + x(iv) x(C)] is in the range of 125 to 160 kDa; Where: Mw(ii) is the average molecular weight Mw of said vinyl copolymer matrix (ii) in component B, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard; x(B) is the proportion of component B in the composition in weight percent; Mw(iv) is the average molecular weight Mw of the vinyl copolymer matrix (iv) in component C, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard; x(C) is the proportion of component C in the composition in weight percent; The composition according to claim 1 or 2.
4. 4. The composition according to claim 1, wherein the vinyl copolymer matrix (ii) has an average molecular weight Mw, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard, of 140 to 200 kg / mol and the vinyl copolymer matrix (iv) has an average molecular weight Mw, measured by gel permeation chromatography in tetrahydrofuran against polystyrene as standard, of 110 to 130 kg / mol.
5. A composition according to any one of claims 1 to 4, wherein components B and C are present in a weight ratio of from 60:40 to 80:
20.
6. 6. Composition according to any one of claims 1 to 5, wherein the dispersed phase (i) of component B has a median diameter D50, measured by ultracentrifugation, of 0.3 to 2.0 μm and the dispersed phase (iii) of component C has a median diameter D50, measured by ultracentrifugation, of 0.3 to 2.0 μm, and at least one of the two dispersed phases (i) and (iii) has a median diameter D50, measured by ultracentrifugation, of 0.7 to 1.5 μm.
7. 7. The composition of any one of claims 1 to 6, wherein components B and C are free of alkali metal, alkaline earth metal, ammonium or phosphonium salts of saturated fatty acids having 8 to 22 carbon atoms, resin acids, alkyl and alkylaryl sulfonic acids, and fatty alcohol sulfates, and components B and C each contain less than 20 ppm of alkali metal and alkaline earth metal ions.
8. The composition according to any one of claims 1 to 7, wherein components B.2 and C.2 consist exclusively of structural units derived from 1,3-butadiene, and components B and C each have a content of structural units derived from 1,3-butadiene of 8% to 12% by weight.
9. As component D, it comprises at least one additive selected from the group consisting of flame retardants, lubricants and release agents, stabilizers, flow promoters, compatibilizers, and dyes and pigments; The composition of any one of claims 1 to 8, which does not contain any further graft polymer prepared by emulsion polymerization.
10. A molding compound made from the composition according to any one of claims 1 to 9.
11. A molded article obtainable from the composition according to any one of claims 1 to 9 or from the molding compound according to claim 10.
Citation Information
Patent Citations
Polycarbonate molding composition
JP2009518472A
Aromatic polycarbonate resin composition and formed part
JP2014001293A
Flame Retardant Polycarbonate Molding Composition i
JP2016501298A
Thermoplastic Resin Composition and Molded Parts Using the Same
US20160319128A1
